Faktor-Faktor yang Mempengaruhi Jiwa Kewirausahaan Pegawai Bank Perkreditan Rakyat - Mohammad Sofyan (Universitas Islam Kadiri, 2019)
This study aims to determine the effect of Education and Training, Professionalism, Work Experience, Leadership, and Work Environment on Employee Entrepreneurship. The sample used in this study were 237 respondents from 15 Rural Banks in Bogor Regency and City. Based on the results of the structural equation model, only Professionalism and the Work Environment have a significant effect on the Entrepreneurship of rural banks Employees